Important African & Modern Masterworks. (New York : Kent Gallery Inc., 1992)
Bambara ; Bamoum ; Bangwa ; Baule ; Keaka ; Kuba ; Lengola ; Lobi ; Mumuye ; Senufo ; Songe ; Urhobo ; Archipenko, Alexander ; Giacometti, Alberto ; Gonzalez, Julio ; Hepworth, Barbara ; Laurens, Henri ; Leger, Fernand ; Lipchitz, Jacques ; Maillol, Aristide ; Miró, Joan ; Moore, Henry ; Picabia, Francis ; Picasso, Pablo ; Rosso, Medardo ; Schmidt-Rottluff, Karl
Important African & Modern Masterworks, Kent Gallery Inc., New York, 24 October - 4 December 1992
boek
Keywords: Afrika